Ketahanan Sosial sebagai Pilar Keutuhan Bangsa di Tengah Tantangan Sosial Kontemporer di Indonesia - Rahayu, ApriliaPutri (Maliki Interdisciplinary Journal, 2025)
Social resilience is a fundamental aspect in maintaining the stability and integrity of a nation. In Indonesia, social dynamics such as disinformation, political polarization, economic disparity, and increasing intolerance are serious challenges for social integration. This article aims to examine the concept of social resilience, the actual challenges faced by Indonesian society, and strategic efforts that can be made to strengthen social resilience at various levels. The method used in this paper is a qualitative-descriptive study based on literature. The findings show that strengthening the value of togetherness, strengthening local communities, digital literacy, and inclusive policies are important pillars in building strong social resilience. By strengthening social resilience, Indonesia has a great opportunity to build a resilient, inclusive, and harmonious society in the face of global social disruption.